Sociomoral Temperament: A Mediator Between Wellbeing and Social Outcomes in Young Children - Narvaez, Darcia; Gleason, Tracy; Tarsha, Mary; Woodbury, Ryan; Cheng, Ying; Wang, Lijuan (Frontiers in Psychology, 2021)
Social outcomes, such as empathy, conscience, and behavioral self-regulation, might require a baseline of psychological wellbeing. According to Triune Ethics Metatheory (TEM), early experience influences the neuropsychology underlying a child’s orientation toward the social and moral world. Theoretically, a child’s wellbeing, fostered through early caregiving, promotes sociomoral temperaments that correspond to the child’s experience, such as social approach or withdrawal in face-to-face situations. These temperaments may represent an individual’s default sociomoral perspective on the world. We hypothesized that sociomoral temperament emerges as a function of wellbeing and would be related to social outcomes measured by moral socialization and self-regulation. Further, we hypothesized that sociomoral temperament would mediate the relationship between wellbeing and social outcomes. To investigate, we collected items reflective of sociomoral temperament, asking mothers from two countries (USA: n = 525; China: n = 379) to report on their 3- to 5-year-old children. They also reported on their child’s wellbeing (anxiety, depression, happiness) and social outcomes, including moral socialization (concern after wrong doing, internalized conduct and empathy) and behavioral self-regulation (inhibitory control and misbehavior). As expected, correlations identified connections between wellbeing, sociomoral temperament, and social outcomes. Mediation analyses demonstrated that sociomoral temperament mediated relations between wellbeing and social outcomes in both samples, though in slightly different patterns. Fostering early wellbeing may influence social outcomes through a child’s developing sociomoral temperament.